Improved angiogenic cell penetration in vitro and in vivo in collagen scaffolds with internal channels. - Yahyouche, A; Zhidao, X; Triffitt, J; Czernuszka, J; Clover, A (2013)
Porous scaffolds are limited in volume due to diffusion constraint and delay of vascular network formation. Channels have the potential to speed up cellular penetration. Their effectiveness in improving angiogenic cell penetration was assessed in vitro and in vivo in 3-D collagen scaffolds. In vitro, channelled and non-channelled scaffolds were seeded with vascular smooth muscle cells. Results demonstrated that the scaffolds supported angiogenic cell ingrowth in culture and the channels improved the depth of cell penetration into the scaffold (P < 0.05). The cells reside mainly around and migrate along the channels. In vivo, channels increased cell migration into the scaffolds (P < 0.05) particularly angiogenic cells (P < 0.05) resulting in a clear branched vascular network of microvessels after 2 weeks in the channelled samples which was not apparent in the non-channelled samples. Channels could aid production of tissue engineered constructs by offering the possibility of rapid blood vessel infiltration into collagen scaffolds.